2004
DOI: 10.1074/jbc.m308893200
|View full text |Cite
|
Sign up to set email alerts
|

Extramembrane Central Pore of Multidrug Exporter AcrB in Escherichia coli Plays an Important Role in Drug Transport

Abstract: We previously reported the crystal structure of the major multidrug exporter AcrB in Escherichia coli (Murakami, S., Nakashima, R., Yamashita, E., and Yamaguchi, A. (2002) Nature 419, 587-593). The extramembrane headpiece of the AcrB trimer contains a central pore composed of three ␣-helices. Each pore helix belongs to a different monomer. In this study, we constructed cysteine-scanning mutants as to the residues comprising the pore helix. Of the 21 mutants (D99C to P119C), 5 (D101C, V105C, N109C, Q112C, and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
66
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 26 publications
5
66
0
1
Order By: Relevance
“…This conclusion is in good agreement with results from several laboratories that indicate that residues in two large periplasmic loops of RND transporters determine their substrate specificity (8,11,12,22,24,27,35).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…This conclusion is in good agreement with results from several laboratories that indicate that residues in two large periplasmic loops of RND transporters determine their substrate specificity (8,11,12,22,24,27,35).…”
supporting
confidence: 81%
“…The proximity of these pockets to the upper portal might allow their connection to the portal upon a conformational change associated with proton transport. It has previously been postulated (27,28) that substrates that accumulate in the central cavity are actively transported into the upper portal space via the channel that should open along the central axis of the structure (solid blue arrows). However, a very significant conformational change associated with channel opening would have to be coupled with proton transport (turquoise arrow) via the transmembrane domain in order to accommodate the passage of substrates.…”
mentioning
confidence: 99%
“…The antibody reaction was performed with an iBind Western system (Life Technologies). An anti-His tag mouse monoclonal antibody was purchased from Sigma-Aldrich (catalog number H1029-0.2ML), and the anti-AcrA and anti-AcrB rabbit polyclonal antibodies that were used were described previously (51). For His tag, AcrA, and AcrB detection, we used 15 g, 2 g, and 15 g membrane protein, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…shown that the inner membrane portion of the RND efflux pumps can recognize and efflux substrates in both the cytoplasm and periplasm of the bacterium (128). Mutation of the periplasmic loops of the P. aeruginosa inner membrane pump component MexB, has shown that substrates are recognized and effluxed from the,periplasmic space and/or the inner membrane (188).…”
Section: Antibiotic Effluxmentioning
confidence: 99%